Heritage keywords: rhetoric and redescription in cultural heritage - Lafrenz Samuels, Kathryn, editor; Rico, Trinidad, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2015)
Situated at the intersection of scholarship and practice, Heritage Keywords addresses the rapidly expanding use of rhetoric within heritage studies, unlocking the potential of fast-standardizing terminology and concepts through projects of 'redescription.' Through attention to the rhetorical edge of cultural heritage, contributors to this volume make plain the innovative reworking of key heritage categories.--Provided by publisher.
Heritage conventions, guidelines, and legal instruments cited -- Notes on contributors -- Introduction: Heritage as persuasion / Kathryn Lafrenz Samuels -- Authenticity: Rhetorics of preservation and the experience of the original / Anna Karlstrom -- Civil society: Civil society in the field of cultural property protection during armed conflict / Sigrid Van der Auwera -- Cultural property: Building communities of stewardship beyond nationalism and internationalism / Alexander Bauer -- Cultural diversity: Cultivating proud and productive citizens in Belizean education / Alicia Ebbitt McGill -- Democratization: The performance of academic discourse on democratizing museums / Cecilia Rodohn -- Difficult heritage: Coming "to terms" with Sicily's Fascist past / Joshua Samuels -- Equity: Polestar or pretense?: international archaeological tourism development in "less developed countries" / Jeffrey Adams -- Heritage at risk: The authority and autonomy of a dominant preservation framework / Trinidad Rico -- Heritage discourse: The creation, evolution, and destruction of authorized heritage discourses within British cultural resource management / Malcolm A. Cooper -- Intangible heritage: What brain dead persons can tell about (intangible) cultural heritage / Klaus Zehbe -- Memory: Towards the reclamation of a vital concept / Gabriel Moshenska -- Natural heritage: Heritage ecologies and the rhetoric of nature / Melissa F. Baird -- Place: Cochiti Pueblo, core values, and authorized heritage discourse / Robert Preucel and Regis Pecos -- Rights: Heritage rights and the rhetoric of reality in pre-revolution Tunisia / Kathryn Lafrenz Samuels -- Sustainability: Primordial conservationists, environmental sustainability, and the rhetoric of pastoralist cultural heritage in East Africa / Paul J. Lane -- After words: A de-dichotimization in heritage discourse / Trinidad Rico.
Keywords: Description (Rhetoric) -- Political aspects; Description (Rhetoric) -- Social aspects; Rhetoric -- Political aspects; Rhetoric -- Social aspects; Historic preservation -- Terminology; Historic preservation -- Study and teaching; Cultural property -- Protection -- Terminology; Cultural property -- Protection -- Study and teaching